The Role of the Company's Basic Strategy for the Company's Development Performance in a Dynamic Environment (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the role of the company's basic strategy in achieving growth and development of the company in a dynamic and rapidly changing environment?Purpose: Explore the types of basic strategy and the role of the company's basic strategy to achieve growth and development in dynamic business environment. The purpose of this research was also to examine the impact of the company's environment on the choice of the company's basic strategy.Method: We made qualitative research, namely the study of a scientific literature. The emphasis is on research by foreign authors.Results: Scientific paper shows the possibilities for further research. It shows the role of the company's basic strategy for the growth and development of the company and the impact that the company's environment has on the process of choosing the company's basic strategy.Organization: An article shows that to achieve growth and development, including their existence on the market, companies must also consider various aspects of the company's environment (ecological environment, social environment, economic environment, technical and technological environment, political and legal environment etc.) when making their strategic business decisions.Society: Companies must consider when chose basic strategy interests and expectations of the company's stakeholders (customers, employees, shareholders, government, competitors).Originality: In the scientific and research literature we have found a lot of research related to the impact of the company's strategies on the performance, growth and development of the company. However, we did not find research that would consider factors arising from the company's environment.Limitations/Future Research: This study presents a scientific paper that is based on a review of scientific research literature in the field under consideration. In the future, we propose quantitative research to demonstrate the impact of the company's basic strategy on the growth and development of the company, considering the impact of the unpredictability of the company's environment on the choice of the company's basic strategy.
Keywords: strategic management; strategic planning; basic strategy; company performance; unpredictability; company environment; planning